Perbandingan Antara Pregabalin Dengan Ibuprofen terhadap Kadar Neutrofil Pascabedah Laparotomi Ginekologi - Muh. Wirawan Harahap; Nasrudin Andi Mappaware; Faisal Sommeng; Noer Fitri Zhachrani; Sobria Munawara (Rumah Sakit Ibnu Sina, Makassar, 2026)
Postoperative pain is an important problem frequently encountered in postoperative patients. Although understanding of the mechanisms of postoperative pain has advanced considerably, postoperative pain management remains suboptimal and is often neglected. Preemptive analgesia refers to the administration of analgesic interventions before nociceptive stimulation occurs, with the aim of preventing pain, suppressing sensory afferent input, reducing central nervous system sensitization, and minimizing postoperative pain effects. This study aimed to compare pregabalin and ibuprofen as preemptive analgesia on neutrophil levels after gynecological laparotomy. This was an experimental clinical trial using a pre-post test control design, in which variables were measured before and after the intervention. The collected data were analyzed using paired t-test and independent t-test. The results showed no significant difference in the increase of neutrophil levels between ibuprofen and pregabalin administration, with a p-value of 0.237. However, the increase in neutrophil levels was higher in the pregabalin group than in the ibuprofen group, namely 683.60 ± 1501.13 compared with 532.82 ± 527.67. Therefore, it can be concluded that there was no significant difference in the increase of neutrophil levels between pregabalin and ibuprofen administration in patients undergoing gynecological laparotomy, although the increase in neutrophil levels was higher in the pregabalin group than in the ibuprofen group.